Connecting Policy and Practice - Kompf, Michael; Denicolo, Pam (Taylor & Francis, 2005)
Written by members of the International Study Association on Teachers and Teaching, the papers in this volume were presented at an international teaching conference on the issues of theory and practice. Using these contributions from experienced researchers, most of whom are practising teachers, this single volume is international in scope and context, demonstrating differences and similarities between and within countries. This detailed book is clearly split into five sections focusing on the following themes: * teacher education - professional identity, professional research, and quality of teacher education * teacher practice - basic values, ethics, and cultural scaffolding * higher education - academic motivation, discourse dissonance concerning intellectual property, self studies of teacher education practice * teacher development - the challenge to be the best teacher, the link between policy and practice, personal theory and practice in tertiary development * research and theory - reflective practice, shared democratic values, teachers as researchers.